Research on the learning/teaching of L2 listening: A bibliometric review and its implications - Lei, Lei; Deng, Yaochen; Liu, Dilin (Studies in Second Language Learning and Teaching, 2023)
This bibliometric study examined the development of research on the learning and teaching of second language (L2) listening from 1948 to 2020 (73 years). Specifically, the study involved: (1) a search and analysis of all the noun phrases to identify important research topics in the abstracts of the published journal articles on L2 listening over the 73 years (divided into three periods) using self-made Python scripts and (2) three co-citation analyses of the references in these articles regarding highly cited authors, publications, and journals, respectively, via the VOSviewer program. The keyword/phrase analysis produced results that helped uncover and delineate the research trends in L2 listening across the three time periods. The co-citation analyses identified the most highly cited authors, publications, and journals as well as the interrelations among the most highly cited items in each of the three categories illustrated with network maps. The results of the analyses and their implications are discussed.